PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN BAHASA INDONESIA MATERI KOSA KATA KELAS 4 SD AL FALAH ASSALAM - Irma Puspitasari Kalake; Yuni Gayatri; Ni Luh Putu Sari Murthi (PROCEEDING UMSURABAYA, 2024)
This study aims to improve the learning outcomes of fourth-grade students in class IV-C at SD AL FALAH ASSALAM through the implementation of the Project Based Learning (PBL) model in vocabulary material. The type of research used is quasi-experimental research. The research design is one group post-test only. The subjects of the study are 20 students from class IV-C at SD AL FALAH ASSALAM for the 2023/2024 academic year. Data collection techniques were carried out through observation and testing. The research instruments used were observation sheets for the implementation of learning, cognitive test sheets, and reflection sheets for both teachers and students. Data analysis was performed using descriptive statistical and qualitative methods. The results of this study indicate that all stages of the Project Based Learning model were implemented well. The student attitude observation results showed 74%, while the student learning outcomes showed 78%, meeting the minimum competency standard (KKTP). The students' presentation skills were at 89%, meeting KKTP. Reflection results revealed that all students enjoyed the learning process and understood the material taught. In conclusion, the implementation of the Project Based Learning model was effective in improving student outcomes.